Imhoff tank under construction. - Unknown:::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows an Imhoff tank used for the reception and processing of sewage under construction near the Heart Mountain Relocation Center.